Clinical Core Laboratory Testing - Molinaro, Ross.; McCudden, Christopher R.; Bonhomme, Marjorie; Saenger, Amy.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2017)
The clinical laboratory is often known as a "black box" to nurses, physicians, and surgeons, but this concise book removes the veil by covering all the pertinent aspects of the clinical laboratory. This book bridges between medicine and chemistry by offering an overview to a clinical laboratory's structure and function, the importance of laboratory utilization and test ordering, as well as pre-analytical, analytical, and post-analytical issues of importance to recognize in any clinical laboratory. An interactive FAQ and a detailed index are also available.
Foreword -- Introduction -- Laboratory Structure and Function -- Laboratory Utilization/Test Ordering -- Pre-analytical Issues in the Clinical Laboratory -- Analytical Issues in the Clinical Laboratory -- Post-Analytical Issues in the Clinical Laboratory -- Index and FAQs.
Keywords: Analytical chemistry; Medicine -- Research; Biology -- Research; Pathology; Analytical Chemistry; Biomedical Research; Pathology